The Dynamism of International Law in Politics:: An Appraisal of Russo-Ukrainian War - Muoneke, Chukwuemeka Vincent; Nnani, Emmanuel Nnaemeka (Journal of Contemporary International Relations and Diplomacy, 2023)
The dynamism of international law when enmeshed in politics is critical especially when superpowers are involved in the violation of international humanitarian and human right laws. The Russia invasion of Ukraine is a vivid example. Russia’s invasion of Ukraine which commenced on 24 February 2022 represented just the latest, albeit most devastating, intervention in a neighbouring former Soviet state. In the effort to examine that, our aims are to critically assess the dynamism of international law in politics through the analysis of the forceful invasion of territorial integrity of Ukraine by Russian government under the leadership of Vladimir Putin in order to underscore the potency of international law when the political interests of a superpowers are involved. In that regard, the paper employed the political realism theory of international relations in the effort to give the work a trajectory narrative. Secondary method of data collection and historical content analysis approach were employed in the collection and analysis of the phenomenon understudy. One of the key findings of this paper is that indeed Russia violated the sovereignty of Ukraine and therefore violated the rules of international law and as a superpower nation the global community seems confused or carefully handling the war in order to avoid the occurrence of another world war. Russia being the current president of the Permanent Members of the UN left the entire nations concerned with worries over the violation of human and humanitarian rights of the Ukrainians. Based on our findings, one of the recommendations put forward is the urgent need for all member states of the UN to take steps to end the conflict as soon as possible in a way that all the interests of the parties are considered. They should comply strictly with the rules of international human right laws and international humanitarian laws to ensure the protection of civilians.